Effects of dietary energy levels on microorganisms and short-chain fatty acids of rumen and tight junction proteins in Honghe Yellow cattle - Yu, Ye; Zi, Yujie; Fu, Runqi; Fu, Binlong; Li, Chenghuan; Lv, Yaqi; Li, Zhe; Wang, Huayu; Leng, Jing (Frontiers in Microbiology, 2024)
This study was conducted to investigate the effects of dietary energy levels on microorganisms and short-chain fatty acids (SCFAs) of rumen and the expression of tight junction proteins in Honghe Yellow cattle. A total of fifteen male Honghe Yellow cattle were randomly divided into three treatments (five replicates per treatment), consisting of formulated energy concentrations of 5.90 MJ/kg (high-energy diet, group H), 5.60 MJ/kg (medium-energy diet, group M) and 5.30 MJ/kg (low-energy diet, group L). The results showed that compared with group H, the expression of Claudin-1 in rumen epithelium of groups M and L was increased, but the expression of ZO-1 was decreased (P <0.05). Moreover, compared with group H, group M down-regulated the expression of Occludin and Claudin-1 in the brain (P<0.05). For rumen bacteria, the dominant phyla included Bacteroidetes and Firmicutes, the abundance of Actinobacteriota in groups M and L was significantly increased compared with group H (P<0.05). At the genus level, the relative abundance of Corynebacterium, Eubacterium_nodatum_group and Neisseraceae in groups M and L was significantly decreased compared with group H (P<0.05). For rumen fungi, the dominant phyla included Basidiomycota, Ascomycota and Neocariastigomycota, the relative abundance of Ascomycetes was significantly higher than that of groups M and L compared with group H (P<0.05). At the genus level, the relative abundance of Neocelimastigaceae and Myceliophthora in groups M and L was significantly reduced compared with group H (P<0.05). Furthermore, the expression of Claudin-1 in rumen epithelium was significantly positively correlated with Actinobacteriota, Corynebacterium and Neisseriaceae. The expression of ZO-1 in the spinal cord was significantly positively correlated with Myceliophthora. The expression of Occludin in brain was positively correlated with valerate content (P <0.05). In summary, dietary energy levels affected the rumen microbiota of Honghe Yellow cattle. The expression of Claudin-1 in rumen epithelium and the total SCFAs concentration were increased with decreasing dietary energy levels, but the expression of Claudin-1 in brain and ZO-1 in the spinal cord were reduced with decreasing dietary energy levels. Meanwhile, the rumen microbiota and SCFAs were significantly correlated with the expression of TJP.